Razpad alfa-AlB12 v zlitinah Al-B in Al-Ti-B - Zupanič, Franc (Kovine zlitine tehnologije, 1998)
In this work it was found out that decomposition of the high-temperature phase @-AIB12 doesn´t occur during cooling of the Al-B and Al-Ti-B alloys from the two-phase region L + AIB12 or the three-phase region L + @-AIB12 + TiB2. It decomposes only in the course of isothermal annealing under -900°C. According to data in the open literature its decomposition should start alredy under 980°C. The decomposition of @-AIB12 takes place by dissolution of @-AIB12 and growth of AIB2. The decomposition rate is higher in ternary Al-Ti-B than in binary Al-B alloys, because TiB2 phase promotes the nucleation of the reaction product AIB2.
Keywords: aluminijeve zlitine; aluminium alloy; titan; bor; železo; silicij; fazna ravnotežja; mikrostruktura